Kimwimbi Women as Mirrored in the Cultural & Social Notions & Expressions - Atieno, Christine; Kathom, Jane (Journal of English Language and Literature (ISSN: 2368-2132), 2019)
Among the Mwimbi linguistic group, expressions exist or are used for a variety of purposes including communication and all are geared towards socialization of societal members so as to enable each fit in their expected caliber. In the social context words and expressions have been used by Mwimbi speakers to explicitly devalue women by normally not saying what they mean. The purpose of this study therefore, is to establish the notions expressed by cultural and social beliefs and practices upon which devaluing of women is based. The objective of this paper is to find out the cultural and social notions and expressions used to devalue women in Kimwimbi Language. Halliday's Social Semiotics Theory was used. A qualitative research design was used. Data was collected in Mwimbi in Ganga Ward Maara sub county, Tharaka Nithi County, Kenya. The population includes all the expressions that contribute to devaluing women in Kimwimbi. Speakers of the language were selected through purposive sampling. Data was collected using focus group discussion guides and a semi structured interview guide. The paper established that the Kimwimbi Language uses expressions that are heavily embedded on cultural and social attitudes to devalue women.